Photos to 'show the world what we're going through': Women use images to talk about living with HIV/AIDS. (23rd August 2012) - Teti, Michelle; Massie, Jenne; Cheak-Zamora, Nancy; Binson, Diane
The growing number of women living with HIV/AIDS (WLH/A) underscores the importance of effective prevention programmes to help women promote their own health and protect their partners from HIV transmission. We elicited WLH/A perspectives about their health promotion and prevention programme needs in a photovoice project called Sharing Stories. Photovoice is a qualitative, participatory research method that uses photography and critical group dialogue to help people identify their health priorities and inform practice. Ten WLH/A participated in the project and took pictures, engaged in group discussions, and planned and held a public photo exhibit. We digitally recorded and transcribed group discussion sessions and performed a content analysis to identify key themes in the data. Women's photos and discussions centred on the importance of: (1) support networks; (2) living healthily with HIV/AIDS; (3) daily stressors and socio-structural challenges, and; (4) growth and transformation. Our findings suggest that prevention and health programmes for WLH/A need to focus holistically on women's physical, mental and social health; help women identify sources of social and emotional support; recognize WLH/A as healthy and capable; and help create healthy structural environments for WLH/A, like appropriate housing. Photovoice was a powerful strategy to motivate meaningful discussions as well as action among WLH/A.